Employment in the Internet: Atypical Features and New Research Approaches - Станислав Александрович Заиченко (Journal of Economic Sociology, 2010)
The paper deals with the different research approaches to the internet employment. Going from the concept of “new economics” the author tries to consider the employment in the Internet from the position of network analysis and the concept of strong and weak ties.  The different forms of Internet employment are analyzed in the paper, as well as social and professional characteristics of those employed by internet. The author draws the boundaries of the internet employment and analyzes the ratio of inside/outside labour market in the internet. The author concludes that internet employment is a developing phenomenon and proposes the further steps of its investigation.